If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5(2x-3)=2(x-3)-75
We move all terms to the left:
-5(2x-3)-(2(x-3)-75)=0
We multiply parentheses
-10x-(2(x-3)-75)+15=0
We calculate terms in parentheses: -(2(x-3)-75), so:We get rid of parentheses
2(x-3)-75
We multiply parentheses
2x-6-75
We add all the numbers together, and all the variables
2x-81
Back to the equation:
-(2x-81)
-10x-2x+81+15=0
We add all the numbers together, and all the variables
-12x+96=0
We move all terms containing x to the left, all other terms to the right
-12x=-96
x=-96/-12
x=+8
| 8x+56=48 | | 8z-7=3z+8 | | 1/9x-6=10 | | -8.5x+14=-5.25x-3.5 | | -21=7(t-90) | | 35+y=61 | | 6x+55=175 | | 12=0.5a4. | | 8v-22=18 | | 1/2(x-8)=31+4x | | c+8/2=c+16/6 | | 13y-14=42 | | 46=u/4+41 | | 17g−19g+–3=19 | | 15=-15a+4a | | y^2+√y-14y+38=0 | | -3(x-4)-(x-4)=2(-4x+3)+1 | | 40+3x=4(-x+5)-36 | | 9n+12-3n=-2n-12 | | k9=2 | | x+4+5x+2+2x-2=180 | | 12(54+w)=42 | | 5g=10+4g | | 4*y=24 | | m/3-18=-9 | | 23x-4=46 | | 5v+14=84 | | 7(y+7)=63 | | -8x-8=64-x | | 1/3(h=6)h=6 | | 6g+18=10 | | 7x=+4x=4x=+28 |